Rooting out hunger - International Food Policy Research Institute (International Food Policy Research Institute, 2012)
From 2007 to 2009, HarvestPlus and its partners disseminated orange sweet potato (OSP) to more than 24,000 households in Mozambique and Uganda to see if we could reduce vitamin A deficiency—through food. All the results are now out, and the evidence makes a strong case for scaling up OSP in Africa.